Penanaman Nilai Kemuhammadiyahan Dalam Upaya Pembentukan Karakter Peserta Didik di SMA Muhammadiyah 3 Jakarta - Ahmad Hudaebiah; Shobah Shofariyani Iryanti (Departement of Mathematics Education, 2024)
This research aims to examine the role and influence of the application or implementation of Muhammadiyah values applied by teachers in forming the character and morals of students at SMA 3 Muhammadiyah Jakarta. The character and morals of students are important in holistic personal development. Muhammadiyah values have a crucial role and influence in shaping the character and morals of students who are religious, civilized and moderate. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. The respondents of this research were school principals, ISMUBA (Islamic, Muhammadiyah and Arabic Language) teachers and students at SMA 3 Muhammadiyah Jakarta. The research results show that Muhammadiyah values have a positive impact in forming the character and morals of students. Through habituation and activities such as the habit of reciting the Quran and Duha prayers in class, assigning imams for Maghrib and Isha prayers as well as social activities (defense of Palestine).